Impact of Reels Video Marketing on Customers’ Purchase Intention - Nur Rizki Faradia Ananda; Erwin Halim (Journal of Social Science, 2022)
This research is motivated by the large number of internet users in Indonesia, as well as the use of Instagram with a variety of useful features provided, one of which is the Reels feature. The purpose of this study is to find out how the influence of the Reel feature on Instagram can have a direct effect on Consumer Buying Interest or it can also be done indirectly through Consumer Brand Attitudes. The sampling technique used is purposive sampling technique. The results of this study indicate that variables based on independent scenarios, user participation, perceived benefits, perceived enjoyment, celebrity involvement directly have a positive and significant effect on consumer brand attitudes, and consumer brand attitudes also have a positive and significant effect on consumer purchase intentions. While interesting content directly (direct effect) does not have a positive and significant effect on consumer brand attitudes.